Antioxidant Activity of Hybrid Grape Pomace Extracts Derived from Midwestern Grapes in Bulk Oil and Oil‐in‐Water Emulsions. (9th August 2015) - Bakota, Erica L.; Winkler‐Moser, Jill K.; Berhow, Mark A.; Palmquist, Debra E.; Liu, Sean X.
Abstract: Natural antioxidants to inhibit oxidation in edible oils are in high demand. Grape pomace is an abundant, inexpensive source of polyphenolic antioxidants, which are responsible for numerous health benefits. We examined pomace from eight varieties of Midwestern hybrid grapes for phenolic content and antioxidant activity. Ethanolic extracts produced from the pomace of each grape variety were added to two model systems, bulk soybean oil and oil‐in‐water emulsions, to determine antioxidant activity. Oxidation was monitored in each model system at a temperature appropriate to that particular system. While the extracts had relatively little effect in bulk oil, we observed dose‐dependent antioxidant effects of some extracts in oil‐in‐water emulsions. Oxidation in bulk oils was assessed via total polar compounds and polymerized triacylglycerols. Oxidation in emulsions was assessed by peroxide value, headspace oxygen measurements, gas chromatography of headspace volatiles, and fatty acid analysis. Pomace extracts derived from red grapes generally outperformed those from white grapes, with the Marechal Foch variety showing high antioxidant activity at intermediate concentrations. At higher concentrations, Marechal Foch, Corot Noir, Frontenac, and Norton extracts showed promising antioxidant activity. This is the first report on antioxidant activity in an oil and emulsion setting for many of these grape varieties.